Pembiayaan Murabahah dalam Perspektif Islam - Muhammad Ismail (STAI Syaichona Moh. Cholil Bangkalan, 2015)
Abstract: Murabahah is a selling and buying transaction with the financial capital is added with the cost and benefits are known as well as agreed by both parties. The essential principles of murabahah consist of sellers, buyers, goods and sighat granted consent. Meanwhile, its requisites are people who are capable to recite murabahah contract law and the pleasure. Terms of traded goods are kosher goods, provide benefits, a full property rights of the sellers and the goods fit the desired specifications of the buyers. The terms of the contract should be clear either on goods specification, prices and not contain clauses that hang the transaction legality. Murabahah law according to the scholars are allowed as long as there is not any binding obligation to complete the transaction, both written and spoken before getting the goods to the ownership and handover.